Electoral Systems - Kurunczi, Gábor (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
The present study compares the electoral systems of the eight countries analysed in this volume based on the specifics of Central Eastern Europe. As a starting point, the study examines the expectations of the electoral system, e.g. the purpose of displaying the will of the electorate as accurately as possible, ensuring stable governance, and aspects such as the size of the country, its traditions or other political considerations. The study undertakes a comparative analysis of the electoral systems of each country primarily on the following issues: how do the electoral system and the political system of a given country interact? How are active and passive voters defined? What are the social reasons for the parliamentary representation of minorities? What impact have these rules had on electoral systems? What common features and differences can be discovered in each national electoral system? How can a given electoral system be evaluated among proportional-majority systems? The chapter concludes that the regulation of electoral systems is always country-specific and in line with social and historical traditions. It is therefore not possible to mechanically take over the electoral system of other countries in any country as some of its elements will not necessarily be compatible with the specificities of the others. The history of the eight countries analysed (the legacy of communism, the ‘problem’ of nationality) shows several points of connection, even though their electoral systems are not uniform. Although most countries – in line with European trends – have proportional electoral systems, these have many different regulations. By comparison, in Hungary (or even in Romania), legislators took a completely different approach in defining the electoral systems after the change of regime. It can thus be stated that the definition of the electoral system is one of the most national issues, where standards can and should be set, but these standards only provide a basis for comparability rather than accountability. KEYWORDS: electoral system, proportionality, majority elements, stable governance, political influence, active and passive suffrage.